Creating the human past : an epistemology of pleistocene archaeology - Bednarik, Robert G., (Archaeopress, 2013)
This text examines systematically both the theoretical and practical issues that have characterized the discipline over the past two centuries. Some of the historically most consequential mistakes in archaeology are dissected and explained, together with the effects of the related controversies. The theoretical basis of the discipline is deliberated in some detail, leading to the diagnosis that there are in fact numerous archaeologies, all with different notions of commensurability, ideologies, and purposes. Their various perspectives of what archaeology is and does are considered and the range of views of the human past is illuminated in this book.